Hubungan Pola Asuh Orang Tua dengan Tingkat Depresi pada Remaja - Manda Virasifani; Betie Febriana; Wahyu Endang Setyowati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Adolescence is a transitional period marked by physical, emotional, and social changes. During this phase, adolescents often experience mental stress that can lead to depression. One factor that impacts a teenager's emotional well-being is their parenting style. Good parenting methods are expected to foster a balanced personality in adolescents and reduce the likelihood of depression. Method: This study employed a quantitative design with a cross-sectional method. The target population was all 327 eleventh-grade students at MAN 1 Pati. Proportional random sampling was used to select the sample, with a total sample size of 136 respondents. Data were collected through a questionnaire on parenting patterns and a questionnaire measuring depression levels (Beck Depression Inventory). The Spearman Rank test was used for data analysis. Results: The results of this study revealed that the most common parenting style adopted by parents was democratic parenting (44.9%), while the most common level of depression experienced by adolescents was moderate depression (54.4%). The Spearman Rank test yielded a ρ value of -0.512 with p = 0.000 (p < 0.05). Conclusion: There is a significant relationship between parental parenting styles and levels of depression in adolescents at MAN 1 Pati.